Peningkatan Hasil Belajar Menulis Cerita Fantasi Melalui Penerapan Model Pembelajaran Berbasis Proyek - Nurfatimah, Nurfatimah; Sultan, Sultan; Sakaria, Sakaria (Fakultas Teknik Universitas Negeri Makassar, 2024)
This study aims to determine the learning outcomes of students' fantasy story writing by applying a project-based learning model. This research is a type of classroom action research. This research consists of four stages, including planning, implementation, observation, and reflection. The subjects of this study were students of class VII.3 UPT SPF SMP Negeri 1 Makassar, consisting of 41 students with details of 13 male students and 28 female students. The data analysis techniques used were qualitative analysis techniques and quantitative analysis. The results of this study showed that there was a significant increase from cycle I to cycle II. In cycle I, student scores began to increase with an average score of 71. Students who were complete in cycle I were 15 students (36.58%), and those who were not complete were 26 students (63.41%). Furthermore, in cycle II, the average student score increased from 71 to 89. In cycle II, all students' scores were complete, and there were no students who were not complete. Thus, it can be concluded that the learning outcomes of writing fantasy stories that have been carried out through cycle II in class VII.3 UPT SPF SMP Negeri 1 Makassar have increased significantly.